1983
DOI: 10.1002/bem.2250040405
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to 60‐Hz electric fields: Effects on the development of the visual‐evoked response in rats

Abstract: Two independent series of experiments were performed on 114 male Sprague-Dawleyderived, albino rat pups, which represented 61 litters in experimental series I and 53 litters in experimental series 11. Animals were exposed for 20 h/day from conception to testing (postnatal days 11-20) to a vertical, 65-kV/m, 60-Hz electric field or sham-exposed.Recordings of the visual-evoked response (VER) were obtained using a small silver ball elcctrode placed epidurally over the visual cortex. Visual stimuli consisted of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Few laboratories have used ERP measures as an endpoint for studies of ELF field effects. Jaffe et al [1983] reported that exposure of rats to a 65-kV/m field from conception to 20 days of age had little effect on the development of the VERP. Dowman et al [1989] exposed monkeys at three levels of combined electric and magnetic fields and evaluated the early sensory components of the visual, auditory, and somatosensory ERPs.…”
Section: Discussionmentioning
confidence: 99%
“…Few laboratories have used ERP measures as an endpoint for studies of ELF field effects. Jaffe et al [1983] reported that exposure of rats to a 65-kV/m field from conception to 20 days of age had little effect on the development of the VERP. Dowman et al [1989] exposed monkeys at three levels of combined electric and magnetic fields and evaluated the early sensory components of the visual, auditory, and somatosensory ERPs.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies at Battelle included the use of a sensitive visual-evoked response test to detect possible subtle effects of an electric field on the developing nervous system of the rat (Jaffe et al 1983). Continuous exposure of rats to a 65-kV/m field from conception to 20 days of age did not affect nervous system development.…”
Section: Figure 21 Exposure System Developed By Battellementioning
confidence: 99%